Important Considerations for Design and Implementation of Decision Aids for Shared Medical Decision Making - Koon, Sean (Perm J, 2019)
INTRODUCTION: Decision aids are software or paper-based tools that enable patients and health care practitioners to work together to make optimal treatment decisions. Although there are decades of favorable research for the use of decision aids, there is wide variation in their development and implementation. OBJECTIVE: To review the literature and provide a summary of best practices for the design, implementation, and assessment of decision aids. METHODS: A literature search and screening process was employed with a focus on systematic review articles. The resulting articles were synthesized and summarized into recommendations regarding the optimal design, implementation, and appraisal of shared decision-making tools. RESULTS: Designers of decision aids should initially focus on engagement by involving health care practitioners and patients to ensure the decision aids are pertinent to the situation and not perceived as time consuming. The International Patient Decision Aids Standards help ensure quality in design. Patients should be able to select information in a manner that suits them and view it in a way that allows them to evaluate trade-offs. In reporting of statistical risks, format bias should be avoided through careful and consistent choice of format and by adding visual representations. Decision aids should be tested in real settings with iterative improvements. For appraisal of the implemented decision aids, consider using the Control Preference and Decisional Conflict scales. DISCUSSION: Further research is recommended regarding optimal engagement of users with decision aids and exploration of the distinct opportunities that computerized decision aids and online patient communities may present. CONCLUSION: Decision aids can be a valuable tool for shared medical decision making. Their quality and usefulness can be maximized by involving users in their creation and by attending to key considerations in their design, implementation, and appraisal.